AUTO- UND SYNSEMANTISCHE FUNKTIONEN VON APHORISMEN IM DEUTSCHEN POLITISCHEN DISKURS - Onishchenko, Natalia; Gubina, O.D. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2015)
The article discusses the functional potential of aphorisms, namely their auto- and synsemantic functions considering their precedency in German political discourse. It is based on the material from electronic archives of German papers and from the electronic archive of the German Bundestag. The article determines the theoretical basis and the linguistic status of aphorisms, precedent texts and political discourse; analyses the functional potential of aphorisms in political discourse; it marks out their convergent and divergent features and defines the basic strategies of political discourse and the specifics of their realization Ьу the means of aphorisms.